Clinicopathological Correlates in a PRNP P102L Mutation Carrier with Rapidly Progressing Parkinsonism‐Dystonia. Issue 4 (18th February 2016) - Umeh, Chizoba C.; Kalakoti, Piyush; Greenberg, Michael K.; Notari, Silvio; Cohen, Yvonne; Gambetti, Pierluigi; Oblak, Adrian L.; Ghetti, Bernardino; Mari, Zoltan
Abstract: Parkinsonism‐dystonia is rare in carriers of the prion protein (PrP) gene ( PRNP ) proline‐to‐leucine substitution at codon 102 (P102L mutation). The severity and distribution of PrP deposition may influence the clinical presentation. The authors present such clinicopathological correlation in a 56‐year‐old man who had a PRNP P102L mutation associated with a phenotype characterized by rapidly progressing parkinsonism‐dystonia. The patient was studied clinically (videotaped examinations, brain magnetic resonance images [MRIs]) and was analyzed using molecular genetics (gene sequence analysis) and neuropathology (histology, immunohistochemistry) during his 7‐month disease course. The patient had parkinsonism, apraxia, aphasia, and dystonia, which progressed rapidly. Molecular genetic analysis revealed his PRNP P102L mutation carrier status. Brain MRIs revealed progressive, global volume loss and T2‐weighted/fluid‐attenuated inversion recovery hyperintensity in the neocortex and basal ganglia. Postmortem examination showed neuronal loss, gliosis, spongiform changes, and PrP deposition in the striatum. PrP immunohistochemistry revealed widespread, severe PrP deposition in the thalamus and cerebellar cortex. Based on the neuropathological and molecular‐genetic analyses, the rapidly progressing parkinsonism‐dystonia was correlated with nigrostriatal, thalamic, and cerebellar pathology.